Overlapping Efforts in the EU Emission Trading System - Fabian Herweg (Center for Economic Studies and ifo Institute (CESifo), 2020)
According to the Phase IV (2021-2030) rules of the EU ETS, the total amount of emissions permits allocated to firms is not fixed but endogenous. This implies that a national climate policy that overlaps with the emission trading system can have an impact on total aggregate emissions. Roughly speaking, if firms increase their holdings of emission permits, the total amount of emissions allocated is reduced. This paper investigates analytically how an overlapping national policy affects the decision of an individual firm and the whole industry to bank emission permits. If marginal abatement costs are not too convex, national climate policies increase banking and thus tend to reduce overall emissions. This effect, however, is reduced in times of low interest rates.
Keywords: D45; Q48; Q58; 330; banking of permits; cap-and-trade; EU ETS; national measures